Challenges in Sustaining the Seal of Good Local Governance: The Case of City of Carmona, Cavite - Sales, Eunice A.; Guevara- Canlas, Michelle; Garcia, Fil Vincent B.; Cid, Maria Charisma A.; Malang, Bernandino P.; Malang, Jocelyn DS. (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study focuses on the City of Carmona, Cavite, and aims to describe the problems the city has in maintaining the Seal of Good Local Governance. It seeks to determine what the challenges are to the Local Government Units’ (LGU) ability to keep the SGLG status, how these challenges affect the city’s operations, then provide recommendations to address these challenges. Based on the data and a "Strongly Agree" consensus from respondents, the Local Government Unit of Carmona has a considerable capacity to sustain its governance practices. This is attributable to the governance framework being grounded on well-defined and institutionalized policies and sufficiency of resources, ability to balance SGLG compliance and SGLG urgent local priorities, and active participation from stakeholders. On the other hand, respondents "Agree" that there are risks to the long-term sustainability of the LGU, which include policy gaps, and unclarity of mandates, inadequate funding, political shifts, the turnover of leadership, natural calamities, and disasters.